Design and performance analysis of ultra-wideband (UWB) antenna for wireless system / Muhammad Irfan Hafiz Mazlan - Mazlan, Muhammad Irfan Hafiz (2025)
This project identifies the signal penetration performance of ultra-wideband (UWB) antenna through different materials, focusing on wood and brick as barriers. The antenna, measuring 35 mm x 45 mm x 1 mm, uses Rogers RT-5880 as the substrate and operates within the 0-12 GHz range. The design process involved selecting microstrip patches, feeding techniques, and ground shapes, followed by simulations using CST Studio Suite software and antenna fabrication. Further analysis involved varying the distance between the antenna and wall materials (wood and brick) and observing the S11 parameters. This study highlights challenges in translating theoretical designs into practical applications, emphasizing the need for precise fabrication, material validation, and experimental optimization. Simulations confirmed the antenna met UWB standards, with a wide bandwidth and reflection coefficient of -10 dB. However, differences between simulated and measured results occurred, with the fabricated antenna exhibiting shifted resonance frequencies, reduced bandwidth, and diminished performance. These issues were attributed to fabrication flaws and environmental factors during measurements. While the simulated antenna performed well under ideal conditions, the fabricated version underperformed in real-world conditions. This project provides understanding on UWB signal penetration, highlighting the need of precise analysis and good antenna design. Future work will be focused on optimising antenna design, performance analysis, and integrating findings into practical applications.